PENERAPAN MODEL QUANTUM LEARNING UNTUK MENINGKATAKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS PADA POKOK BAHASAN KEDUDUKAN DAN PERAN ANGGOTA KELUARGA SISWA KELAS III SD NEGERI 81 KOTA TERNATE - Arifin, Amir (Jurnal GeoCivic, 2024)
This type of research is classroom action research (PTK). The research was carried out in two cycles, each cycle consisting of four stages, namely planning, implementation, observation, reflection. The research subjects were class II students at SD Negeri 81 Ternate City, totaling 32 students consisting of 17 girls and 15 boys. Data collection was carried out through observation, tests, and documentation. The data collection instruments used are observation sheets, test assessment guidelines, and documentation. Data analysis techniques are descriptive qualitative and quantitative.In cycle I all actions can be carried out according to the action plan. Of the 32 students who completed, 12 students or 37.5, while 22 students or 62.5 did not complete. So an average of 65.5 can be obtained (cycle I). Meanwhile, in cycle II with the same material, all actions were carried out according to the action plan. This is proven by the number of 32 students who completed as many as 24 students or 75.0 while those who did not complete were 8 students or 25.0 with an average of 83.75 (cycle II). Meanwhile, the results of student learning activities were with a percentage of 67.5 (cycle I) and 85.0 (cycle II) and the results of teacher activities were with a percentage of 65.0 (cycle I) and 84.61 (cycle II). The results of the research show that the application of the QL (Quantum Learning) model is to improve student learning outcomes in social studies learning on the subject of the position and role of family members of class II students at SD Negeri 81 Ternate City.